Characteristic Features of Phonetic Labarotorias - Uktamovich, Marufov Elyor (International Journal on Integrated Education, 2023)
this article gives information about the phonetic laboratory, its types, practical and theoretical aspects, tasks, methods of using it, virtual learning of languages, social psycholinguistic features of oral speech.